Pelatihan Lesson Study Bagi Guru SD di Kecamatan Pontianak Kota - Nurcahyo, Muhammad Aqmal; Afryaningsih, Yunika; Fatmawati, Risdiana Andika; Setyowati, Dessy (Politeknik Negeri Pontianak, 2024)
Learning practices that occur in West Kalimantan, including in Pontianak are still found to be conventional and conceptual. Implementation of learning in the classroom is still teacher-centered rather than student-centered. Such a pattern certainly will not contribute much to improving the quality of education and obtaining better learning outcomes. Innovation needs to be done to overcome conditions like this in the hope that teachers can present meaningful learning and provide experiences to students. Lesson study activities can be used as an alternative to encourage changes in learning in Indonesia to be more optimal and effective. The method used in this community service activity is in the form of outreach, the practice of preparing lesson study designs, and implementing lesson study in class. Community service activities through lesson study training provide several benefits, such as: (1) mutually beneficial collaboration between teachers; (2) there is an increase in teacher skills in developing innovative lesson design in schools; (3) there is a change in the pattern of learning interaction in class; and (4) increased active participation and high-order thinking skills of students.